14-3-3[zeta] and aPKC-[iota] synergistically facilitate epithelial-mesenchymal transition of cholangiocarcinoma via GSK-3β/snail signaling pathway - Yang, Yan; Schemmer, Peter (OncoTarget, 2016)
Cholangiocarcinoma (CCA) invasion and metastasis are the primary causes of poor survival rates in patients. The epithelial-mesenchymal transition (EMT) is a crucial step in cancer invasion and metastasis. However, it is still unclear of the molecular mechanism. In this study, the expression of 14-3-3ζ and atypical protein kinase C-ι (aPKC-ι) was further detected in CCA tissues and cell lines. Meanwhile, we established the EMT model of CCA cells and investigated 14-3-3ζ and aPKC-ι co-regulatory effect on the EMT in vitro and in vivo. Further, we identified the downstream molecular glycogen synthase kinase 3 beta (GSK-3β)/Snail signalling pathway that contribute to regulating the EMT. Our data showed that the expression of 14-3-3ζ and aPKC-ι was synergistically increased in CCA tissues compared with adjacent noncancerous tissues and was intimately associated with differentiation and the tumour-node-metastasis (TNM) stage. Multivariate Cox regression analysis indicated that high 14-3-3ζ and aPKC-ι expression separately predicted a poor prognosis and were independent prognostic indicators in patients with CCA. The CO-IP experiment confirmed that the mutual binding relationship between 14-3-3ζ and aPKC-ι. Small interfering RNAs and siRNA rescue experiment demonstrated that 14-3-3ζ and aPKC-ι regulated each other. In addition, 14-3-3ζ and aPKC-ι pretreatment by si-RNA inhibit the phosphorylated GSK-3β and Snail expression during EMT. Meanwhile, silence of 14-3-3ζ or aPKC-ι suppressed CCA cells migration, metastasis and proliferation in vitro and in vivo. Our study demonstrates that 14-3-3ζ and aPKC-ι synergistically facilitate EMT of CCA via GSK-3β/Snail signalling pathway, and may be potential therapeutic target for CCA.
Gesehen am 13.03.2018